1982
DOI: 10.1063/1.92934
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium passivation of grain-boundary dangling bonds in silicon thin films

Abstract: Hydrogen passivation of silicon grain boundaries has been investigated by using deuterium as a readily identifiable isotope which duplicates hydrogen chemistry. Deuterium detection with high sensitivity was achieved with secondary-ion mass spectrometry. Diffusion of deuterium in single- crystal silicon and polycrystalline silicon thin films at low temperatures (e.g., 350 °C) clearly demonstrates enhanced diffusion along grain boundaries. Defects at grain boundaries were detected by electron-spin resonance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
53
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(57 citation statements)
references
References 12 publications
0
53
1
1
Order By: Relevance
“…It is considered that the bond angle distortion and the lattice relaxation occur simultaneously. In addition, it is probable that the dehydrogenation 9,10) occurs simultaneously by LPX irradiation. These phenomena influence the diffusion of Si atoms.…”
Section: Resultsmentioning
confidence: 99%
“…It is considered that the bond angle distortion and the lattice relaxation occur simultaneously. In addition, it is probable that the dehydrogenation 9,10) occurs simultaneously by LPX irradiation. These phenomena influence the diffusion of Si atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental estimates of the diffusion constant are numerous and vary widely, [1][2][3][4][5][6][7] sometimes by two orders of magnitude at a given temperature, as can be appreciated from the open circles in Fig. 1(a).…”
mentioning
confidence: 99%
“…In general, grain boundaries can limit the optoelectronic properties of materials due to a high density of dangling bonds and impurity segregation caused by differences in diffusion behavior as compared to the bulk material. [10][11][12] Analyzing our TF-VLS p-InP via a combination of secondary ion mass spectroscopy (SIMS) and capacitance-voltage (CV) profiling revealed that only ~10% of the incorporated Zn was electrically active in our TF-VLS p-InP, leading to the possibility that much of the interstitial Zn accumulates at the interfaces and along grain boundaries. 8 Moreover, the bulk material quality of single crystal InP can differ from thin-film InP as well, which is caused by structural differences inherent to the growth process such as dislocations, twin boundaries and related defects.…”
Section: Introductionmentioning
confidence: 99%